Ultrastructural study of the follicular epithelium in oocytes of Pachycondyla (Neoponera) villosa ants (Hymenoptera: Ponerinae) - Izabel, Maria [UNESP] (1998)
Insect oocytes are surrounded by the follicular epithelium which is simple and cuboidal, with the mainly functions of: synthesis of vitellin membrane and chorion and synthesis and transport of hemolymph products (proteins). In Pachycondyla (Neoponera) villosa ants workers aged less than 10 days do not present the formation of ovarian follicles (oocytes, nurse cells and follicular cells) indicating that vitellogenesis starts at approximately 10 days of age. Studies of participation of the follicular epithelium in Pachycondyla (Neoponera) villosa showed that in stage I oocytes the epithelium does not present the opening of intercellular spaces. In stage II these spaces begin to be observed together with separation of the follicular epithelium from the oocyte surface. In stage III two types of material were observed in the intercellular spaces: electrodense material in the basal region and compacted material in apical one as well as follicular epithelium/oocytes interface suggesting that the extraovarian material that reach oocytes undergoes some type of modification during passage through the intercellular spaces. The follicular epithelium spaces in queen are bigger than in workers oocytes.